A concise history of the participation of the hellenic army in the first world war 1914-1918 - Καρατζάς, Αριστείδης Δ. (An Army History Directorate Publication, 1999)
This work narrates the military operations carried out in the Balkans during the First World War, as well as the political events that took place in Greece and eventually forced it to abandon its neutrality and join the allies. The first part covers the period from the World War inception till the first operation taking place in the Balkans and Greece's entry to the War when the second part covers our country's involvement in the war and describes all the military operations, conducted in the Balkan from May 1918 until the end of the War. Appendices, official charts, various tables and charts of photographic material are also included in this issue. A list of old and current names of the toponyms is also included in the last pages of this issue.